Marketing Strategy of Ayodya Resort Bali Hotel Through E-Commerce (Website) in Optimizing Room Occupancy Level - Ni Kadek Sudiasih Ari Artini Putri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to identify effective website-based e-commerce marketing strategies to increase room occupancy at Hotel Ayodya Resort Bali using a descriptive qualitative method and SWOT analysis. Data were collected through interviews, observation, documentation, and literature review, and analyzed using IFAS, EFAS, the IE Matrix, and the SWOT Matrix. IFAS results highlight key strengths, such as the hotel's strategic location and strong brand reputation (score 0.60), while weaknesses include low digital adaptability among staff (score 0.10), with a total IFAS score of 2.95. EFAS analysis shows opportunities in digitalization trends (score 0.60) and threats from intense five-star hotel competition (score 0.30), totaling 2.70. The IE Matrix places the hotel in the